Day-to-Day Blood Pressure Variability and Risk of Dementia in a General Japanese Elderly Population: The Hisayama Study. Issue 6 (8th August 2017) - Oishi, Emi; Ohara, Tomoyuki; Sakata, Satoko; Fukuhara, Masayo; Hata, Jun; Yoshida, Daigo; Shibata, Mao; Ohtsubo, Toshio; Kitazono, Takanari; Kiyohara, Yutaka; Ninomiya, Toshiharu
Abstract : Background: Several observational studies have reported that higher visit-to-visit blood pressure variability is a risk factor for cognitive impairment and dementia. However, no studies have investigated the association of day-to-day blood pressure variability assessed by home blood pressure measurement with the development of dementia. Methods: A total of 1674 community-dwelling Japanese elderly without dementia, ≥60 years of age, were followed up for 5 years (2007–2012). Home blood pressure was measured 3 times every morning for a median of 28 days. Day-to-day systolic (SBP) and diastolic blood pressure variabilities, calculated as coefficients of variation (CoV) of home SBP and diastolic blood pressure, were categorized into quartiles. The hazard ratios and their 95% confidence intervals of the CoV levels of home blood pressure on the development of all-cause dementia, vascular dementia (VaD), and Alzheimer disease (AD) were computed with a Cox proportional hazards model. Results: During the follow-up, 194 subjects developed all-cause dementia; of these, 47 had VaD and 134 had AD. The age- and sex-adjusted incidences of all-cause dementia, VaD, and AD increased significantly with increasing CoV levels of home SBP (all P for trend <0.05). These associations remained unchanged after adjustment for potential confounding factors, including home SBP. Compared with subjects in the first quartile of CoV levels of home SBP, the risks of the development of all-cause dementia, VaD, and AD were significantly higher in those in the fourth quartile (hazard ratio=2.27, 95% confidence interval=1.45–3.55, P <0.001 for all-cause dementia; hazard ratio=2.79, 95% confidence interval=1.04–7.51, P =0.03 for VaD; hazard ratio=2.22, 95% confidence interval=1.31–3.75, P <0.001 for AD). Similar associations were observed for CoV levels of home diastolic blood pressure. Meanwhile, home SBP levels were significantly associated with the risk of VaD but not with the risks of all-cause dementia and AD. There was no interaction between home SBP levels and CoV levels of home SBP on the risk of each subtype of dementia. Conclusions: Our findings suggest that increased day-to-day blood pressure variability is, independently of average home blood pressure, a significant risk factor for the development of all-cause dementia, VaD, and AD in the general elderly Japanese population. Abstract : Supplemental Digital Content is available in the text.